2013
DOI: 10.7287/peerj.preprints.47
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Stiffness without mineral: material properties and biochemical components of jaws and chondrocrania in the Elasmobranchii (sharks, skates, and rays)

Abstract: 26Chondrichthyians (sharks, ratfish, and rays) can function at extremes (growing big, swimming 27 fast, and eating hard-prey) suggesting their skeletons are experiencing loading regimes equal to 28 or greater than those of other fishes. In most vertebrates, cartilage is a soft connective tissue 29 serving two purposes; a low-friction bearing surface and contour filler; however, cartilaginous 30 fishes maintain a skeleton made of cartilage throughout life. We examined material properties 31 and biochemical comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 1 publication
(2 reference statements)
0
3
0
Order By: Relevance
“…The apparatus was placed into elasmobranch ringer's solution (Forster et al, ) for at least 30 min to allow the putty to set. Once set, the putty had an elastic modulus of 3.19 GPa, which is three orders of magnitude higher than the modulus of articular cartilage and about one order of magnitude higher than that of previously tested mineralized shark cartilage (Korhonen et al, ; Jin and Lewis, ; Stolz et al, ; Porter et al, 2006, 2013; Macesic and Summers, ; Ferrara et al, ; Huber et al, ; Liu et al, ; ). The hyomandibula was then placed in the materials testing machine so the discs were parallel with the compression platens and the hyomandibula could be loaded along the longitudinal axis (Fig.…”
Section: Methodsmentioning
confidence: 78%
See 2 more Smart Citations
“…The apparatus was placed into elasmobranch ringer's solution (Forster et al, ) for at least 30 min to allow the putty to set. Once set, the putty had an elastic modulus of 3.19 GPa, which is three orders of magnitude higher than the modulus of articular cartilage and about one order of magnitude higher than that of previously tested mineralized shark cartilage (Korhonen et al, ; Jin and Lewis, ; Stolz et al, ; Porter et al, 2006, 2013; Macesic and Summers, ; Ferrara et al, ; Huber et al, ; Liu et al, ; ). The hyomandibula was then placed in the materials testing machine so the discs were parallel with the compression platens and the hyomandibula could be loaded along the longitudinal axis (Fig.…”
Section: Methodsmentioning
confidence: 78%
“…This strategy of hypermineralization is reminiscent of the thick outer layers and even trabeculation of the jaw cartilages in hard prey crushing stingrays and sharks (Summers, ; Summers et al, ). Three studies have reported values for the stiffness of unmineralized cartilage (), with one finding values ranging from 20 to 776 MPa (Porter et al, ), one ranging from 0.15 to 5.56 MPa (Liu et al, ), and the third ranging from 9.97 to 35.90 MPa (Ferrara et al, ). Though these values for stiffness range widely, many of the values for hyomandibular cartilages fall above those for unmineralized cartilage, and most of the stiffness is likely due to the level of mineralization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation